Are Most and More Than Half Truth-Conditionally Equivalent?. (24th February 2022) - Denić, Milica; Szymanik, Jakub
Abstract: Quantifying determiners most and more than half are standardly assumed to have the same truth-conditional meaning. Much work builds on this assumption in studying how the two quantifiers are mentally encoded and processed (Hackl, 2009 ; Lidz et al., 2011 ; Pietroski et al., 2009 ; Steinert-Threlkeld et al., 2015 ; Szymanik & Zajenkowski, 2010 ; Talmina et al., 2017 ). There is however empirical evidence that most is sometimes interpreted as 'significantly more than half' (Ariel, 2003, 2004 ; Ramotowska et al., 2020 ; Solt, 2011, 2016 ). Is this difference between most and more than half a pragmatic effect, or is the standard assumption that the two quantifiers are truth-conditionally equivalent wrong? We report two experiments which demonstrate that most preserves the 'significantly more than half' interpretation in negative environments, which we argue to speak in favor of there being a difference between the two quantifiers at the level of truth conditions.